(Police and guards in the Abbasid era (132-247 - NIKISH, ISMAIL HASAN (Journal of Humanities & Social Sciences, 2019)
The knowledge of the activity of the police and guards in the golden age of the Abbasid state، as the police are important institutions، which played an important role in the political and administrative life in the state، so this research came to know the nature of the activity played by this device. And this device could not carry out this important activity only if it is headed by a person who has the qualities to be provided by the following of this device of science and sophistication and know what to do so so this study dealt with a group of the most important figures of the police who had a long history in drawing The policy of the state and also to intervene in various political and military conflicts to give one over to another.